The politics of the anti-realist trend in contemporary Philippine fiction - Fajutagana, Leonora M. (2009)
Among the most conspicuous trends in literary practice is the increasing bias for non-realist narrative modes in fiction which reflects, among others, the postmodern skepticism towards positivist discourses. This paper considers this a major shift and explores some of its implications on the novel as genre and on literature in general.

Evidences of the novel's break from its realist roots abound in contemporary Philippine novels in English, including the historical novel which has been most tied up to the realist tradition by virtue of its empirical, documentary basis. The current trend thus indicates significant revisions in the conceptualization of the genre and possibly, also of historiography. In view of the current cultural turn of criticism where texts are invariably read for their ideological underpinnings, the trend could signify some directions for the political use of the genre. For whereas the realist text has been indicated for its complicity in western hegemony and rendered inappropriate for current critical purposes, the emerging non-realist modes ought to hold more promise in terms of challenging old styles identified with dominant ideologies and structures.

A survey of Philippine historical novels in English reveals a range of non-realist strategies favored by contemporary Filipino novelists, particularly magic realist and romantic embellishments, Bakhtinian carnivalesque and polyphony and meta fictional self-reflexibility. Because they tend towards excess of representation and stress transgressions of norms and boundaries, these strategies undercut such key realist premises as plausibility and verisimilitude and thus point to major revisions of the genre. That these strategies serve to inspire skepticism rather than certainty further underscores the novel's break positivism and its potential for a radical critique.
Keywords: English novel